2022
DOI: 10.3389/fpain.2022.809352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nociception in a Preclinical Episodic Migraine Model by Dietary Supplementation of Grape Seed Extract Involves Activation of Endocannabinoid Receptors

Abstract: Migraine is associated with peripheral and central sensitization of the trigeminal system and dysfunction of descending pain modulation pathways. Recently, dietary inclusion of grape seed extract (GSE) was shown to inhibit mechanical nociception in a preclinical model of chronic temporomandibular joint disorder, a condition often comorbid with migraine, with the antinociceptive effect mediated, in part, by activation of 5-HT3/7 and GABAB receptors. This study further investigated the mechanisms by which GSE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Thus, the GSE-mediated increase in the functional expression of the GABAB receptor via upregulation of GABAB1 in trigeminal neurons could directly oppose the cellular effects of stimulatory agents such as nitric oxide and cytokines that facilitate CGRP release ( Bowen et al, 2006 , Durham et al, 2006 ). This change in neuronal receptor expression would allow for more GABA binding, which could partially explain some of the inhibitory effects of GSE observed in preclinical orofacial pain models ( Cady et al, 2010 , Cornelison et al, 2020 , Cornelison et al, 2021 , Woodman et al, 2022 ). Increased activation of the GABAB receptors is known to promote potassium efflux, inhibition of calcium influx, and a decrease in cyclic AMP levels in the neurons, resulting in a lower neuronal excitability state ( Padgett and Slesinger, 2010 , Evenseth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the GSE-mediated increase in the functional expression of the GABAB receptor via upregulation of GABAB1 in trigeminal neurons could directly oppose the cellular effects of stimulatory agents such as nitric oxide and cytokines that facilitate CGRP release ( Bowen et al, 2006 , Durham et al, 2006 ). This change in neuronal receptor expression would allow for more GABA binding, which could partially explain some of the inhibitory effects of GSE observed in preclinical orofacial pain models ( Cady et al, 2010 , Cornelison et al, 2020 , Cornelison et al, 2021 , Woodman et al, 2022 ). Increased activation of the GABAB receptors is known to promote potassium efflux, inhibition of calcium influx, and a decrease in cyclic AMP levels in the neurons, resulting in a lower neuronal excitability state ( Padgett and Slesinger, 2010 , Evenseth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 ). Previously, we demonstrated that dietary inclusion of GSE functions to enhance descending inhibitory pain signaling in preclinical models of migraine and TMD via activation of serotonergic, GABAergic, and endocannabinoid receptors to suppress central sensitization ( Cornelison et al, 2021 , Woodman et al, 2022 ). Further, the cellular effects of GSE were shown to involve upregulation of basal levels of the enzyme MKP-1, which inactivates the pro-inflammatory MAP kinases, and the glutamate transport proteins GLAST and GLT-1 to lower the extracellular concentrations of this stimulatory neurotransmitter ( Cady, Hirst et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine Woodman et al (2022), further investigated how GSE inhibits mechanical nociception in a preclinical model of episodic migraine. In an injury-free paradigm of migraine-like pain, GSE supplementation decreases trigeminal pain signals by activating endocannabinoids and inhibiting the production of CGRP centrally.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…In an injury-free paradigm of migraine-like pain, GSE supplementation decreases trigeminal pain signals by activating endocannabinoids and inhibiting the production of CGRP centrally. GSE may therefore be helpful as an additional migraine therapy (Woodman et al, 2022). The authors of a study by Slavin et al called their investigation Using spice and grape pomace extracts to affect migraine-related indicators in vitro.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%